Quantitation of Ivosidenib, A Novel Mutant IDH1 Inhibitoron Mice DBS: Application to a Pharmacokinetic Study - Dittakavi, Sreekanth; Jat, Rakesh Kumar; Mullangi, Ramesh (Drug Research, 2019)
Ivosidenib is an approved drug for relapsed or refractory IDH1 mutant AML patients. The goal of the present work is to develop and validate an LC-MS/MS method for the quantitation of ivosidenib in mice dried blood spots (DBS) as per regulatory guideline in the linearity range of 1.10–3293 ng/mL. To date there is no bioanalytical method reported for quantitation of ivosidenib. The chromatographic resolution of ivosidenib and internal standard (warfarin) was achieved on a C18 column with an isocratic mobile phase. All validation parameters met the acceptance criteria. The intra- and inter-day precision was in the range of 2.79–10.5 and 5.76–9.02%, respectively. Ivosidenib was stable for 3 freeze/thaw cycles, up to 7 days at room temperature and for one month at −80°C. The applicability of the validated method is shown in a mice pharmacokinetic study. Ivosidenib was quantifiable up to 24 and 36 h following intravenous and oral administration to mice, respectively. The oral bioavailability was 48%. Comparison of DBS vs. plasma concentrations of ivosidenib showed excellent correlation, indicating DBS can be used as an alternative for plasma for pharmacokinetic analysis.
Keywords: lvosidenib; dried blood spot; LC-MS/MS; method validation; mice blood; pharmacokinetics